Twórcze kształcenie. Utopia czy rzeczywistość = Creative education - utopia whether reality - Magda-Adamowicz, Marzenna (Zielona Góra: Uniwersytet Zielonogórski)
Authoress speaks about creative teacher, which it creates innovations, changes and system of work modifies. In creative education intellectual activity is careful behind most important, practical, learnedly sie through uncovering as well as most important creative atmosphere of work is.
Keywords: twórczość; edukacja